WHATSAP (WANITA HAMIL TANPA ASAP ROKOK) - Qurrotu Aini; Merlyna Suryaningsih; Luluk Fauziyah Januarti (STIKES NGUDIA HUSADA MADURA, 2020)
Cigarette smoke is smoke that is mixed between smoke and particles. This smoke consists of 4000 chemical compounds mixed, including poisonous substances and 69 of them are cancer-causing substances. Based on data and information obtained from the head of the PKK Perum Perumahan Graha Mentari, there were 8 pregnant women who reported being exposed to cigarette smoke. This happens because in his house there are family members who smoke This community service will be carried out at Graha Mentari Housing with a series of activities as follows: pregnant women and families will be given material about the dangers of smoking through counseling activities, this counseling will be held for approximately 30 minutes with a 10-minute material delivery session and discussion session 20 minutes. PKK and pregnant women at the Graha Mentari Housing participated in the activity. The activity was given material about the dangers of smoking through counseling activities. for pregnant women after counseling about the dangers of smoking and anemia in pregnant women, 100% of pregnant women already know well about the material presented, namely with an understanding level of 75%. With this we hope that there will be no interference with pregnancy, anemia in pregnant women and in general the health status of pregnant women can be improved, especially for pregnant women in Graha Mentari housing.